2019
DOI: 10.1080/02724634.2019.1645148
|View full text |Cite
|
Sign up to set email alerts
|

A new Monodontidae (Cetacea, Delphinoidea) from the lower Pliocene of Italy supports a warm-water origin for narwhals and white whales

Abstract: In this paper we reexamine the taxonomy and systematic position of the Eocene stingrays from Bolca Lagerstätte which are traditionally assigned to Urolophus crassicaudatus (Blainville). The analysis of their tooth morphology supports an assignment to the Eocene stingray genus Arechia Cappetta, a taxon known from isolated teeth from the Ypresian-Lutetian of northern and western Africa. The teeth of the Bolca specimens differ from the type species A. arambourgi in some characters (i.e., labial face with concave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…17) relies in the presence of well-distinct longitudinal labial ridges at the crown base. Personal observations by the present authors on an unpublished tooth set of Pachyscylli um from some Pliocene localities of Tuscany (including the lower Pliocene vertebrate-bearing site of Arcille; Bianucci et al 2019) revealed that the presence of a smooth labiobasal margin of the crown represents a stable dental character of Lawley's species, GAMPS-00924 being indeed the sole examined Tuscan Pliocene Pachyscyllium tooth that bears "distans-like" longitudinal labial ridges at the crown base. Consequently, we agree with Reinecke et al (2011) in regarding P. distans as a valid, separate species that significantly differs from P. dachiardii (and not just a result of sexual dimorphism or any other form of intraspecific heterodonty).…”
Section: Systematic Palaeontologymentioning
confidence: 64%
See 1 more Smart Citation
“…17) relies in the presence of well-distinct longitudinal labial ridges at the crown base. Personal observations by the present authors on an unpublished tooth set of Pachyscylli um from some Pliocene localities of Tuscany (including the lower Pliocene vertebrate-bearing site of Arcille; Bianucci et al 2019) revealed that the presence of a smooth labiobasal margin of the crown represents a stable dental character of Lawley's species, GAMPS-00924 being indeed the sole examined Tuscan Pliocene Pachyscyllium tooth that bears "distans-like" longitudinal labial ridges at the crown base. Consequently, we agree with Reinecke et al (2011) in regarding P. distans as a valid, separate species that significantly differs from P. dachiardii (and not just a result of sexual dimorphism or any other form of intraspecific heterodonty).…”
Section: Systematic Palaeontologymentioning
confidence: 64%
“…Following the emergence of modern palaeontological research standards, however, these historical collections have lost some of their scientific importance due to widespread uncertainties regarding their geographical and stratigraphic context (Landini 1977;Cigala Fulgosi et al 2009;Collareta et al 2016). Now however, the recent reports of rare and elusive elasmobranch taxa from the Pliocene deposits of Tuscany (Spadini & Manganelli 2015;Collareta et al 2017a;Collareta et al 2017b;Manganelli & Spadini 2019), as well as the discovery of new fossil localities that are rich in shark and ray teeth (Bianucci et al 2019), are contributing to shed new light on the late Neogene cartilaginous fish faunas of the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…), Rajidae (Rostroraja olisiponensis) and Rhinobatidae (Rhinobatos sp.) (Bianucci et al 2019;Merella et al 2020;Fig. 2).…”
Section: Geological and Palaeontological Settingmentioning
confidence: 99%
“…Other vertebrate remains from this deposit include five skeletons of the extinct dugongid sirenian Metaxytherium subapenninum, two skeletons of billfish (Makaira sp. ), and the holotype and only known specimen of the archaic monodontid cetacean Casatia thermophila; moreover, teeth of sparid teleosts are very common (Sorbi et al 2012;Tinelli 2013;Bianucci et al 2019;Merella et al 2020). Fossils of macro-invertebrates are abundant in the vertebrate-bearing intervals exposed at Arcille; they are mostly represented by bivalves (mostly pectinids and venerids, including the extinct large-sized clams Callista italica and Pelecyora gigas) but also include gastropods, scaphopods, echinoids, bryozoans, ahermatypic corals (Flabellum?…”
Section: Geological and Palaeontological Settingmentioning
confidence: 99%
See 1 more Smart Citation